Optimized conversion of waste vegetable oil to biofuel with Meta heuristic methods and design of experiments - Van Huong Dong; Prabhakar Sharma (BIORE Scientia Academy, 2023)
Biodiesel generated from waste cooking oil (WCO) shows enormous potential for accomplishing SDGs and embracing circular economy principles. This strategy coincides with SDGs 7 and 12, which promote clean energy along with ethical consumerism, by converting waste cooking oil into biofuel. It reduces dependency on fossil fuels, reduces emissions, and promotes sustainable energy sources. Furthermore, using WCO biodiesel adheres to the circular economy concept, reducing waste and pollution while conserving resources (SDGs 12, 14, and 15). To optimize this process, a hybrid technique comprising RSM, ANOVA, and particle swarm optimization is being explored. Researchers achieved 90% biodiesel production employing this technology, encouraging both eco-friendly energy and resource-efficient practices. The optimized parameters produced remarkable results: 82.98% biodiesel generation with a reaction time of 101 minutes, 2% catalyst, and a methanol-to-oil ratio of 20%, demonstrating the potential of this integrated strategy.